MECHANISM OF FILTRATION DRYING OF ORGANIC MATERIALS OF FIBROUS STRUCTURE AND RESULTS OF RESEARCH OF EXTERNAL HEAT EXCHANGE - Botagoz M. Kaldybayeva; Arlan Zh. Abilmagzhanov; Dauren Zh. Dzhanabayev; Zagira S. Kobeyeva (Academic Scientific Journal of Chemistry, 2020)
One of the high-intensity methods for removing both free and bound moisture is filtration drying. This is due to the fact that during filtration drying, the heat agent is filtered through the porous structure of the wet material, which is placed on the perforated partition in the direction "wet material–perforated partition". The velocity of the heat agent in the pores and channels of a stationary layer of wet material determines the thickness of the boundary layer (hydrodynamic, thermal, and diffusion) and, accordingly, the values of the heat and mass transfer coefficients. In addition, the surface of heat and mass transfer is the total surface of the pores and channels through which the heat agent is filtered. The filtration rate of the heat agent is determined based on technical and economic considerations, given that its increase affects the growth of pressure loss. Moreover, the actual speed of the heat agent relative to the layer elements is much higher than in the case of drying by any other methods (in a fluidized bed, during drying in pneumatic transport dryers, etc.). Large heat and mass transfer surfaces and the speed of the heat agent in the pores and channels of the stationary layer of wet material provide high heat and mass transfer coefficients and, accordingly, the intensity of filtration drying. This article presents the results of the study of external heat exchange between the heat agent and dry particles of organic materials of fibrous structure, in particular raw cotton and its stems, and the mechanism of filtration drying.